Effects of Medicinal Plants on Human Hosts and Zoonotic Helminthic Infections: A Systematic Review - Heidari-Soureshjani, Saeid; Sherwin, Catherine M.T. (Natural Products Journal, The, 2021)
Parasitic worm infections are a major health issue around the world, which cause numerous physiological damages in the patient's infected organ(s). The aim of this review was to investigate the anthelmintic properties of various medicinal plants. In this systematic review, all Randomized Controlled Trials (RCTs), quasi-experimental and experimental studies examining the anthelmintic effects were retrieved from databases, including Institute for Scientific Information (ISI) and PubMed from 1988-2019 by interesting keywords. In vitro and in vivo studies have demonstrated that many medicinal plants, including their compounds and derivatives, have anthelmintic properties through various Mechanisms Of Action (MOA). Examples of MOAs include paralysis of the helminths’ central nervous system, tegumental (outer body covering) destruction, interference with enzyme functioning, increased autophagy and apoptosis and reduction in cell viability and count. These actions lead to a reduction in the helminth ability to reproduce, decrease in egg count, inhibition of energy generation, damage to digestive tissues, lipid and ion accumulation, and change in and binding to different regulatory proteins and disruption of the helminth motor activity. These MOAs can also be used for the treatment of parasitic worms. Medicinal plants and their compounds have been the primary sources of new therapeutics, and are comparably more cost-effective than synthetic drugs and provide effective methods to combat parasitic worms that have entered into the human body. Therapists must take into account the effective dose of these compounds in treating the patients and also consider their overall health status, including comorbidities. There is an urgent need to conduct clinical trials using certain approaches, such as clinical interventional trials, to identify the effectiveness of herbal medicines in treating human host and zoonotic helminthic infections.
Keywords: medicinal plants